Alternative splicing in mesenchymal stem cell differentiation. (15th July 2020) - Park, Jung Woo; Fu, Siyi; Huang, Borong; Xu, Ren-He
Abstract: The differentiation and maturation of mesenchymal stem cells (MSCs) to mesodermal and other lineages are known to be controlled by various extrinsic and intrinsic signals. The dysregulation of the MSC differentiation balance has been linked to several pathophysiological conditions, including obesity and osteoporosis. Previous research of the molecular mechanisms governing MSC differentiation has mostly focused on transcriptional regulation. However, recent findings are revealing the underrated role of alternative splicing (AS) in MSC differentiation and functions. In this review, we discuss recent progress in elucidating the regulatory roles of AS in MSC differentiation. We catalogue and highlight the key AS events that modulate MSC differentiation to major osteocytes, chondrocytes, and adipocytes, and discuss the regulatory mechanisms by which AS is regulated. : Abstract : Mesenchymal stem cells (MSCs) are essential cell sources for bone, fat tissues, cartilage, and other connective tissues inside the body and in the test tube. Alternative splicing of pre-mRNAs, which encode critical determinants of MSC differentiation, regulates the MSC differentiation by specifying cell type-specific transcriptome or antagonizing the function of the WT protein.